The subtle balance of trust: how employees’ expected and perceived trust influence impression management - Zhang, MinMin; Ma, Xiaodong (Frontiers in Psychology, 2025)
IntroductionThis study examines how employees expected and perceived trust influence impression management strategies, focusing on their interplay in shaping pro-social and self-oriented behaviors. Trust is pivotal in organizations, yet research has overlooked the impact of trust mismatches on impression management. Addressing this gap, we analyze the effects of trust congruence and explore behavioral variations under different trust combinations.MethodsUsing a quantitative approach, we analyze survey data from employees across various enterprises. To test the hypotheses, we first conducted polynomial regression analysis, followed by response surface analysis. The primary polynomial regression aims to test the hypotheses of ascendant ridge, consistency, and asymmetry, further revealing the complex relationships between the variables.ResultsTrust congruence fosters pro-social impression management and curtails self-oriented behaviors. Higher trust levels correlate positively with pro-social behaviors. Notably, trust incongruence has asymmetric effects: employees with high expected but low perceived trust resort to self-oriented strategies, while those with low expected but high perceived trust exhibit stronger pro-social tendencies.DiscussionThese findings highlight the need to promote trust congruence in management. Addressing trust misalignment through tailored strategies, such as enhancing communication and support, can foster constructive behaviors. Future research should explore trust dynamics and moderating organizational factors like leadership and culture. This study advances understanding of workplace trust and offers practical insights for management.